Peranan Masjid Sebagai Pusat Pendidikan Agama Islam dalam Membentuk Karakter Remaja di Masjid Nurul Hasanah Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Elma Zahara; Ali Imran Sinaga; Miswar Miswar (Jurnal Budi Pekerti Agama Islam, 2025)
This study aims to determine the character of youth at the Nurul Hasanah Mosque, Percut Sei Tuan District, Deli Serdang Regency, to determine and describe the role of the Nurul Hasanah Mosque, Percut Sei Tuan District, Deli Serdang Regency as an educational center for youth, and to determine the supporting and inhibiting factors in shaping the character of youth at the Nurul Hasanah Mosque, Percut Sei Tuan District, Deli Serdang Regency. This study uses a qualitative research method with data collection techniques through observation, interviews, and documentation. The data sources and informants of the researcher are the administrators of the Nurul Hasanah Mosque, teachers/mentors of the Nurul Hasanah Mosque, youth at the Nurul Hasanah Mosque, and parents of youth at the Nurul Hasanah Mosque. The results of this study indicate that youth at the Nurul Hasanah Mosque have prominent characters, including being religious, enthusiastic, tolerant, and appreciating achievement. The mosque plays an important role not only as a place of worship, but also as a center for youth education. through programs such as memorizing the Qur'an, regular studies, and social activities.